Delinquency in Poland in the years 1954 to 1958 in the light of police statistics (Archives of Criminology, 1960)
From the years 1945-1946 down to the present moment Polish police statistics have undergone a number of transformations and improvements concerning the collection of data, their elaboration, as well as the scope of the information collected. Judging on the basis of data coming from the years 1956-1957, about 90 per cent of the criminal cases made over to the law-courts with an indictment went through the hands of the police. The majority of the remaining 10 per cent of cases were dealt with direct by the Public Prosecutor’s Office (cases for a great variety of serious offences) or else by certain administrative organs (cases of minor forest thefts, tax offences, minor frauds in commerce, and a few others). In this way, police statistics may be considered as a source which makes it possible to form a relatively full picture of the offences brought to light in Poland.Certain transformations have also been undergone by the problem of the statistical unit accepted by police statistics. While previously (down to 1956-1957) such a unit was a criminal case (which might comprise a larger number of them), at present such a unit, in principle, consist of one offence. By offences, in police statistics, are understood felonies or misdemeanors, i.e. acts dealt with by the 1932 Criminal Code, still in force, or by special penal statutes, and for which the penalty is over three months custody or a fine of over 4500 zlotys.The statistical material contained in the present contribution has not been published so far, apart from the basic information provided by the Statistical Year-Books for the years 1956, 1957, and 1958.The number of the population of Poland increased from about 27 000 000 to 29 000 000 during the 1954 to 1958 period, while the number of city and town dwellers increased from about 11 300 000 to 13 500 000, and that of  village dwellers decreased from 15 700 000 to 15 500 000 in the same period.In the course of the above-mentioned period, therefore, the number of offences known to the police increased by 35 per cent, but the rate of delinquency, in connection with a certain increase in the total number of the population, increased only by 27 per cent.In the period preceding the Second World War, in the years 1927 to 1937, the number of offences brought to light every year was considerably larger (in 1934 as many as 658 thousand were registered, and in the years 1935 to 1937 nearly 600 thousand per annum); the rate of delinquency was expressed by the following coefficients: in 1934 - 2000, in 1935 - 1770, in 1936 - 1760, and in 1937 - 1710.The magnitude of delinquency in the years 1954 to 1958 differed considerably as between the territories of the several voivodeships. The highest rate of delinquency could be observed in the voivodeships of the Western Territories, with the exception of the voivodeship of Opole (in the several years of the period under investigation coefficients oscillated between 1450 and 2130), in the two largest cities: Warsaw (2470 b 2760) and Łódź (1590 to 1970), as well as in the most highly industrialized and urbanized region of the country' formed by the voivodeship of Katowice (1400 to 1680). Nearly one-third of all the offences known to the police were committed on the territory of a mere three voivodeships (those of Katowice, Wrocław, and the City of Warsaw), which contain rather over one-fifth of the country's population.The offences brought to tight by the police have been divided into four groups according to their kind: group I consists of offences against property, group II - of economic offences, group III – of offences against life and health, and group IV – of all the other offences.Offences against property, which comprise the accaparation of social property, thefts of individual property, robberies, frauds, forgeries, and damage to property, in 1954 and 1955 constituted about 70 per cent of all the offences brought to light (the number of such offences known to the police in these years was 214 470 and 238 911 respectively), in 1956 and 1957 about 65 per cent (241 543 and 261 621 offences respectively), and in 1958 about 60 per cent (251 788 offences). Their rate, in the years 1954 to 1958, was expressed by the figure of from 780 to 920 offences per 100 000 of the population. In the 1954 to 1958 period, approximately 91 000 to 124 000 offences of accaparating social property were brought to light annually, while their number kept continually increasing down to 1957; in 1958 about 117 000 of them were made known to the police.It is a generally known and emphasized fact that the size of the obscure figure is particularly big with offences against property. It is to be presumed that this obscure figure is most conspicuous in the case of offences against social property.Among the offences against social property between 11 000 and 15 000 were burglaries. Out of a total of 11 989 of such offenses brought to light in 1958, 24 per cent were committed in the country (so that there were 188 of them for each 100 000 village dwellers), and 76 per cent - in the cities and towns (there were 679 of them per 100 000 of the population).According to the size of the cities and towns, the coefficients which depict the number of burglaries per 100 000 of the population assumed the following proportions: towns of up to 50 thousand inhabitants - 622, from 50 to 100 thousand inhabitants - 651, 100 to 200 thousand inhabitants - 676, and over 200 thousand inhabitants - 810.During the 1954 to 1958 period an approximate annual figure of from 111 000 to 131 000 thefts of individual property was known to the police, but as from 1955 their number diminished from year to year reaching the figure of 112 883 in 1958. Of the latter offences, 31 per cent were committed in the country (coefficient: 230), and 69 per cent in the cities and towns (coefficient:580). In the case of theft of individual property there was also a dependence between the size of the towns and the rate of such offences: in towns with a population below 50 thousand it was expressed by a coefficient of 470, in towns of between 50 and 100 thousand inhabitants - 720, from 100 to 200 thousand inhabitants - 620, over 200 thousand inhabitants - 750.Thefts of individual property with burglary amounted to 11 577 in 1958 (and their number has kept decreasing from year to year, starting from 1955, when 18 455 of them were known to the police. 13 per cent of them have been committed in the country (coefficient 154), and 87 per cent in the cities and towns (coefficient 689). According to the size of the towns, going from the smallest to the largest, the coefficients showing the rate of such offences were expressed in the following figures in 1958: 397, 918, 929 and 1067.If we count together the accaparation of social property and thefts of individual property and treat them jointly as thefts, it would appear that in the years 1954 to 1958 from 200 000 to 245 000 such offences were made known to the police every year; their rate was expressed by the figure of from 750 to 860 per 100 000 of the population.In the years 1954 to 1957 from 3000 to 4000 forgeries were known to the police every year; their number has tremendously increased in 1958, reaching the very figure of 6300 (i.e. 217 per 100 000 of the population).The number of robberies brought to light by the police amounted to 2066 in 1954 (coefficient:76), 2503 in 1955 (coefficient: 91), 2905 in 1956 (coefficient: 103), 3185 in 1957 (coefficient: 112), and 2503 in 1958 (coefficient: 89). The decrease in the number of such offences recorded in 1958 is estimated as connected with a real decrease in their number. Of the total of robberies known to the police in 1958, 35 per cent were committed in the country (thus there were 46 of them per 100 000 of the population), and 65 in the cities and towns (138 per 100 000 of the urban population).According to the size of the towns (from the smallest to the largest) the coefficients depicting the rate of robberies committed there looked as follows: 85, 141, 194, 213.The number  of  cases of receiving stolen goods has considerably increased within the 1954 to 1958 period, from 816 in 1954 (coefficient: 32), to 1880 in 1958 (coefficient: 65).Group Two of offences, described by the name of economic offences, has been made to include cases of speculation, corruption and neglect of duty by civil servants resulting in damage to the State economy, further, Treasury offences, and currency offences. In the years 1954 to 1957 from 36 000 to 40 000 such offences were known to the police every year; in 1958 their number has considerably increased, probably in connection with a greater diligence in prosecuting them, and amounted to as many as 53 579 (coefficient: 190).Group Three - that of offences against life and health - comprises: murder and manslaughter, infanticides, inflicting grievous injury to the body, and brawls. The total number of such offences has very considerably increased in the years 1954 to 1958, namely from 18 583 in 1954 (coefficient: 70) to 28 910 in 1958 (coefficient: 100), i.e. by about 60 per cent. Their share among all the offences recorded by the police has increased from 13 per cent in 1954 to 21 per cent in 1958.In the years 1954 to 1958 from 700 to 900 murders and manslaughters were recorded annually; in 1958 803 of them were known to the police, of which 620 were carried out and 183 attempted. Consequently there were 28 such offences per 100 000 of the population that year. In 1937 3 314 murders and manslaughters were recorded, i.e. 96 per 100 000 of the population.The number of infanticides recorded by the police did not go beyond the figure of 90 per year (in 1958 there were 75 such cases). In 1937 802 infanticides were brought to light.The number of recorded cases of inflicting grievous injury to the body and of participation in a brawl (with using a dangerous tool or else if death or grievous injury to the body were the result) has very considerably increased in the years 1954 to 1958 from 5 508 in 1954 (coefficient: 204) to 10 005 in 1958 (coefficient: 346).In 1954 6146 cases of inflicting serious or very serious injury to the body were known to the police (coefficient: 227), in 1958 – 8 350 (coefficient: 289).In 1954 6123 cases of inflicting slight bodily harm were record ed (coefficient: 227), and in 1958 _ 9677 (coefficient: 335).Of the offences included in Group Four particularly noteworthy are the offences against morality. In 1958 969 cases of rape were recorded; 901 cases of immoral acts with juveniles under 15 years of age, and 290 cases of abetting to prostitution and deriving profits therefrom.In the Polish text, the present contribution is supplemented with an annex which provides the more important items of the information collected by the police concerning road accidents, suicides, and prostitution.